Analysis of storage capacity and energy conversion on the performance of gradient and double-layered porous electrode in all-vanadium redox flow batteries. (1st August 2019) - Chen, Wei; Kang, Jialun; Shu, Qing; Zhang, Yunsong
Abstract: In the general monolayer electrode of constant porosity, the conflict between the available specific surface area and the hydraulic permeability is a momentous hinder in designing the high-performance electrodes of VRFB. In this paper, several novel electrode structures with gradient or double-layered porous media (GPM or DLPM) are installed in the stack to decouple the conflict and connection between hydraulic permeability and specific surface area. Ten kinds of electrode structures with constant, linear or stepwise decreasing/increasing porosity respectively are designed and compared. The lower concentration polarization loss, higher cell energy efficiency and capacity in the stepwise and linear increasing of porosity profiles are related to the electrolyte flow uniformity in porous electrode and alleviation of conflict between permeability and specific surface area. The higher pumping losses in these arrangements serve as deteriorative factor. In the stepwise increasing porosity mode, the effects of the thickness ratio between two porous layers with different porosities, electrode thickness and porosity variation amplitude were investigated. There is an optimum thickness ratio and electrode thickness to obtain the saturated cell capacity and more energy efficiency, and the rise amplitude of porosity will reduce the system efficiency while increasing the cell capacity. Highlights: The novel gradient and double-layered porous electrodes are designed. Flow in porous electrode is related to concentration overpotential. More advantage can be obtained in VRFB due to the utilization of SIP at R = 1:3. Porosity variation amplitude between two porous layers is investigated.